Leg ulcer treatment by superficial vein surgery and saline-gauze dressing - Dagilaitis, Rolandas; Triponis, Vytautas; Gudgalytė, Ingrida; Triponienė, Dalia (Lietuvos chirurgija, 2007)
Rolandas Dagilaitis, Vytautas Triponis, Ingrida Gudgalytė, Dalia Triponienė Vilnius University Centre of Vascular Surgery, Antakalnio str. 57, LT-10207 Vilnius, Lithuania E-mail: vytautas.triponis@mf.vu.lt Objective To determine the effectiveness of phlebectomy and topic saline in patients with leg ulcer caused by isolated superficial vein reflux. Materials and methods One hundred and thirty consecutive patients with 143 ulcers were operated for superficial varicose veins and venous ulcer. Patients with deep reflux, peripheral arterial disease (ankle/brachial index <0.9), diabetes, history of circular venous ulcer, malignancies, mental disorders, musculoskeletal diseases limiting patient’s physical activity and edema of non venous origin were excluded from the study. Past history data were recorded by questionnaires which included the duration of the ulcer, the number of recurrences, characteristic of compression therapy and topic agents used for ulcer care. Ulcer size was evaluated according to its largest dimension. Operations were performed under regional anaesthesia. All patients were followed at 1, 3, 6, 12 and 24 months. No compression therapy was advocated postoperatively. Results Ulcer manifestation span was from 1 to 33 years, 6.47±0.55 years on the average (p < 0.0001). Preoperative compression therapy was inadequate in all patients, local treatment was carried out with large range of antiseptic solutions. Postoperative healing rate at 3 months was as follows: 95.8% for ulcers < 3 cm , 79% and 37.7% for ulcers 3-6 cm and >6 cm respectively. The healing process was complete in 135 (94.4%) ulcers at 1 year. One healed ulcer (0.7%) recurred between 6 and 12 months, 7 ulcers >6 cm showed reepithelialization being in process. Conclusion Phlebectomy in cases of isolated superficial vein reflux is able to heal venous ulcers in majority of patients. The healing rate was correlative with ulcer size and duration. Surgery plus saline-gauze local treatment significantly reduced the costs of venous ulcer treatment. Key words: leg ulcer, superficial vein surgery, topical treatment